Benefits of integrating educational tech tools in virtual learning environments - Trejo González, Gabriela María
In this modern era, where technology’s advancement is growing exponentially, and with this growth, every aspect of human existence is changing for the better, technology has made positive impacts in developing our modern world, and the Education area is not an exception, or at least that is the purpose of integrating Educational Technology tools in virtual classrooms or in hybrid teaching modalities. Educational Technology is here to make things easier, not only for educators but for learners around the world. Thanks to technology teachers can prepare lessons and assignments more asila and quickly, they can make use of different tools to make those lessons more interactive and engaging for students, they can correct exercises automatically allowing instant feedback, they can monitor each student individually, or detect when a student is not following the pace of the course. These are just a few of the benefits that technology has brought to the classroom. Through a thorough exploration of recent studies, this paper showcases how the incorporation of educational tech tools enhances students’ engagement, fosters personalized learning experiences, and boosts critical thinking skills among students. The integration of Educational Technology in education streamlines processes, empowers educators, engages students, and fosters critical thinking skills. By highlighting these advantages and providing valuable insights into the potential of implementing different EdTech tools in virtual learning environments, these abstract aims to encourage educators to integrate EdTech tools in their study plans and objectives of their courses and ultimately help learners succeed in an increasingly digital world